Pattern of Growth Retardation and Sexual Maturation in Children having Beta Thalassaemia - Chhabra, Gurpreet Singh; Sodhi, Manmeet Kaur (Journal of Nepal Paediatric Society, 2016)
Introduction: Thalassaemia is a group of genetic disorders of blood, characterized by decreased synthesis of one of two types of poly peptide chain (α or ß) that form a normal adult human haemoglobin molecule (Hb A- α2 ß2). This results in decreased filling of red cell with haemoglobin and anaemia. Retardation of growth and delayed sexual maturation can occur as a complication of thalassaemia. The objectives of this study were to study the pattern of growth failure and sexual maturity rate (SMR) in children with β-thalassaemia major, and to compare it with controls. Material and Methods: In this case-control study conducted simultaneously at two centres at Bebe Nanki Mother And Child Care Centre, Amritsar and Sri Guru Ram Das Charitable hospital, Amritsar, the growth parameters (height,weight and sexual maturation ) and serum ferritin levels of a total of 114 patients aged 8-16 years (64 males and 50 females) with β-thalassaemia major were compared with those of 100 healthy controls of the same age and gender. Results: Underweight was observed in 89(78.1%) of patient group and 9(9%) of control group. Short stature was observed in 64(56.1%) patients and 7(7%) of the control group. The mean age of menarche for female thalassaemia patients was 12.11±2.1 years and for control females was 11.42±1.11years, The SMR were delayed in 108(95%) of patients and in 6 (6%) of controls. The level of serum ferritin was found to be significantly associated with delayed SMR in thalassaemia patients. Conclusion: Growth failure and delayed SMR significantly occur in thalassaemia patients, when compared to the controls. Adequate chelation therapy can help in controlling serum ferritin levels and thereby facilitating normal physical growth and sexual development in chronically transfused thalassaemia patients. J Nepal Paediatr Soc 2016;36(1):56-60